Covid-19 in Italy : Impact of Lockdown in Italy on Socio-Economic Situation - Yogie Nugraha (Syntax Corporation Indonesia, 2021)
The COVID-19 outbreak in Italy ranks third most in the world with very continued growth over time. The purpose of this article is to discuss the case of COVID-19 in Italy and its impact on socioeconomic life as well as international relations between Italy and other countries. This article uses library reviews to perform analysis related to the topic of this article using sources such as academic journals, research reports, news articles and so on.